(untitled) (Research, Society and Development, 2022)
The research aims to study the theory of dialogue of sources in the harmonization of civil law and civil procedural law in the case of the action of consignment in payment dealing with joint and several obligation of successive treatment, in the context of the creditor’s delay and when configured by the institutes of objective good faith. Using the deductive method with doctrinal review as a methodological option, the analysis of the theory of the dialogue of sources begins, demonstrating the harmony and coordination between the legislations of the legal system for the realization of normative values. Next, the active joint and several obligations of successive treatment and the attached duties of good faith are analyzed. In conclusion, the systematic dialogue of complementarity of the sources of civil law and civil procedure in the filing of the action of consignment in payment dealing with mora accipiendi, configured the objective good faith, allows the coexistence of laws with fields of different applications, which dialogue in the same fluid and complex legal system.